Self-Induced Injury of the Periodontal Tissues - V Kini; D G Nayak; A Uppoor (Wolters Kluwer Medknow Publications, 2006)
Self-induced injuries are inflicted based on habit, frequently associated with psychogenic background; related only in the manner by which they are produced, bearing no particular anatomic, etiologic or microscopic similarities. The following case report attributes a suspicious periodontal lesion to self-induced injury.